PALS1 is a key regulator of the lateral distribution of tight junction proteins in renal epithelial cells - Groh, Ann-Christin (2024)
The evolutionarily conserved apical Crumbs (CRB) complex, consisting of the core components CRB3a (an isoform of CRB3), PALS1 and PATJ, plays a key role in epithelial cell-cell contact formation and cell polarization. Recently, we observed that deletion of one Pals1 allele in mice results in functional haploinsufficiency characterized by renal cysts. Here, to address the role of PALS1 at the cellular level, we generated CRISPR/Cas9-mediated PALS1-knockout MDCKII cell lines. The loss of PALS1 resulted in increased paracellular permeability, indicating an epithelial barrier defect. This defect was associated with a redistribution of several tight junction-associated proteins from bicellular to tricellular contacts. PALS1-dependent localization of tight junction proteins at bicellular junctions required its interaction with PATJ. Importantly, reestablishment of the tight junction belt upon transient F-actin depolymerization or upon Ca2+ removal was strongly delayed in PALS1-deficient cells. Additionally, the cytoskeleton regulator RhoA was redistributed from junctions into the cytosol under PALS1 knockout. Together, our data uncover a critical role of PALS1 in the coupling of tight junction proteins to the F-actin cytoskeleton, which ensures their correct distribution along bicellular junctions and the formation of tight epithelial barrier.